Polemik Talak di Luar Pengadilan: Analisis Hukum Positif dan Perspektif Mazhab Syafi'i terhadap Perlindungan Hak Perempuan di Indonesia - Nilhakim (Cendekia Inovatif Dan Berbudaya, 2026)
Extrajudicial divorce remains a recurring legal and social problem in Indonesia because the Shafi'i school, which is influential among Indonesian Muslims, regards a husband's valid pronouncement as capable of dissolving a marriage without judicial confirmation, whereas Indonesian positive law recognizes divorce only through a court process. This normative study examines that tension and its implications for women's rights by applying statutory, conceptual, comparative, case-law, and maqasid al-shari'ah approaches. Primary materials include the Marriage Law, the Religious Courts Law, the Compilation of Islamic Law, Supreme Court regulations and chamber formulations, and authoritative Shafi'i legal texts. The study finds that extrajudicial divorce may be considered religiously effective within classical Shafi'i doctrine, but it does not terminate marital status under Indonesian state law. The distinction should not be framed as a direct contradiction: classical fiqh regulates religious validity, while state law regulates public proof, legal consequences, and enforceability. Judicial divorce is therefore a legitimate procedural restriction based on public interest and siyasa shar'iyya. It protects women by securing iddah maintenance, mut'ah, child support, custody arrangements, marital-property claims, and documentary certainty. Supreme Court policy through PERMA No. 3 of 2017 and subsequent chamber formulations strengthens gender-responsive adjudication by allowing and structuring post-divorce obligations. The article proposes a harmonization model in which a prior extrajudicial pronouncement is treated as a religious fact requiring immediate judicial regularization, not as a substitute for court divorce. This model better fulfills legal certainty, justice, and the protection of life, lineage, property, and dignity.